If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1z = -8 Solving 6 + -1z = -8 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1z = -8 + -6 Combine like terms: 6 + -6 = 0 0 + -1z = -8 + -6 -1z = -8 + -6 Combine like terms: -8 + -6 = -14 -1z = -14 Divide each side by '-1'. z = 14 Simplifying z = 14
| X^4-4*x^3+8x= | | y=x^2+1.5xfor-2 | | 2(0)+7y=28 | | y-14=-11 | | 21x+3=17x+15 | | 3t-2=5t+4 | | (7b-1)-2(3b+3)=-2 | | 50x+13=12 | | 3(x^2-5(x+2(3-5x)))= | | 7-z=5 | | 10-6z=-62 | | 21x+3+17x+15=180 | | X^2n-5=11 | | 3-z=-10 | | 10-d=37 | | 12x+1+3*(x+5)=1 | | 90+.5x=50+.9x | | 3cos(6x)sin(5y)=4 | | 4(g+7)=68 | | 2x^2+4x-117=0 | | -4x+5x-8+4=-3x+5-9 | | W-5=-(5-w) | | 64x^2-kx=1 | | 8x^3=64 | | 18x-x+30=0 | | 13d+560m=595 | | 4(2x+7)=-2(x+6)-1 | | 16d+760m=754 | | 1+0.8x+0.6x^2=0 | | (17b-2)-8(2b+3)=-4 | | 8x+4(x+-13)=4 | | 17d+560m=595 |